Suspected placenta accreta and cesarean hysterectomy: observational cohort utilizing an intraoperative decision strategy. (March 2016) - Weiniger, Carolyn F.; Kabiri, Doron; Ginosar, Yehuda; Ezra, Yossef; Shachar, BatZion; Lyell, Deirdre J.
Abstract: Introduction: Planned cesarean hysterectomy (CH) is recommended to minimize morbidity for suspected placenta accreta (PA), yet this ends fertility. We examined CH frequency and post-operative morbidities for suspected PA cases when an intra-operative decision strategy to perform CH was used. Methods: Suspected PA cases were pre-operatively identified in one tertiary care center. Women were assessed intra-operatively, prior to uterine incision, for immediate CH or for attempted placental separation. We compared outcomes among women with versus without PA (surgical and/or pathologic diagnosis), and examined outcomes following immediate CH versus attempted placental separation. Results: Our cohort, from 2002 to 2012, comprised 99 women with suspected PA; 54 (54.5%) had PA diagnosed by surgery/pathology, and 45 (45.5%) did not. Among women diagnoses surgically or pathologically with PA, CH was performed for 46/54 (85%); 8 women with suspected PA had successful placental separation. 27 of the 46 CH were performed immediately following uterine wall examination and 19 were performed following attempted placental separation. We received histological confirmation of the clinical placenta accreta diagnosis for 24/46 (52.2%) cases, and in 22/46 (47.8%) cases the histology did not confirm the clinical diagnosis. Surgery duration, packed cell transfusion requirement and postoperative outcomes were similar among women with PA regardless of immediate CH versus attempted placental separation, except for a higher cystotomy rates following attempted placental separation. Emergency deliveries were performed at significantly earlier gestational ages. Discussion: Among women with suspected PA, an intra-operative CH decision allows some women to avoid CH. Consideration of attempted placental separation did not increase blood transfusion or post-operative complications, but was associated with a higher rate of cystotomy.